1984
DOI: 10.1073/pnas.81.8.2396
|View full text |Cite
|
Sign up to set email alerts
|

Production of platelet-derived growth factor-like molecules and reduced expression of platelet-derived growth factor receptors accompany transformation by a wide spectrum of agents.

Abstract: A series of nontransformed human and murine cells and derivative cell lines transformed by methylcholanthrene; by simian virus 40, Kirsten and Moloney murine sarcoma viruses, simian sarcoma virus, and adenovirus; and by a "spontaneous" event in culture were examined for the expression of receptors for the platelet-derived growth factor (PDGF) and for production of substances able to compete with 1251-labeled PDGF for binding to the cell-surface PDGF receptor. In each case, transformation resulted in a 50-100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
71
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(76 citation statements)
references
References 27 publications
5
71
0
Order By: Relevance
“…Recently it has been shown that the 28-kDa protein encoded by the simian sarcoma virus (SSV) oncogene, v-sis, is structurally (11,18,44), antigenically (27,34), and functionally (9,17,29,43) very similar or identical to one of the chains of PDGF. A variety of transformed cell lines is known to produce PDGF-like growth factors, including glioma (28) and osteosarcoma (15) cells, a series of transformed fibroblasts (6), simian virus 40 (10)-and SSV (29)-transformed cells, embryonal carcinoma cells (13), and probably also T cells infected with human T-cell leukemia virus (47). For some of these cell lines, production of PDGF-like molecules can be correlated with expression of the c-sis oncogene (12,47).…”
mentioning
confidence: 99%
“…Recently it has been shown that the 28-kDa protein encoded by the simian sarcoma virus (SSV) oncogene, v-sis, is structurally (11,18,44), antigenically (27,34), and functionally (9,17,29,43) very similar or identical to one of the chains of PDGF. A variety of transformed cell lines is known to produce PDGF-like growth factors, including glioma (28) and osteosarcoma (15) cells, a series of transformed fibroblasts (6), simian virus 40 (10)-and SSV (29)-transformed cells, embryonal carcinoma cells (13), and probably also T cells infected with human T-cell leukemia virus (47). For some of these cell lines, production of PDGF-like molecules can be correlated with expression of the c-sis oncogene (12,47).…”
mentioning
confidence: 99%
“…However, it remains to be established whether these in vitro observations might have in vivo relevance in disorders characterized by intravascular coagulation, myelofibrosis, or vasculitis. In addition, since PIDGF-like molecules are produced in vitro by transformed cells (27)(28)(29)(30), these observations may be pertinent to clonal disorders of the hematopoietic stem cell with abnormal release of cell products. It is also possible that PDGF-like molecules made by endothelial cells (30,31), smooth muscle cells during development (32) or after injury (33), and macrophages (Shimokado, K., E. W. Raines, and R. Ross, submitted for publication), may modulate erythropoiesis within their microenvironments.…”
Section: Discussionmentioning
confidence: 99%
“…The PDGF is angiogenic and is known to stimulate the reproduction and chemotaxis of connective tissue cells and matrix deposition. 21 Though PRP was the first platelet concentrate to be invented, its preparation involved biochemical handling and the use of potential immunogenic material; hence, PRP is not a strict autologous material. 22,23 Choukroun's PRF is a simple strategy of concentrating platelets or enriching blood clot which acts as a bioscaffold and reservoir of growth factors for tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%